The postgraduate research handbook : succeed with your MA, MPhil, EdD and PhD - Wisker, Gina (Palgrave study guides, 2008)
An accessible, rigorous guide through research for all postgraduate students including international students, largely involved in MA, MPhil, EdD and PhD study. Advice, support and both active and reflective tasks take readers through the stages of research. These range from choosing a university and a topic, writing proposals, developing appropriate methodology and methods, carrying out the research, to dealing with the findings and writing up. It also considers such social and cultural issues as working with your supervisor and with other researchers, giving presentations and writing for publication, and being prepared for a successful viva.